2012
DOI: 10.1148/radiol.12120638
|View full text |Cite
|
Sign up to set email alerts
|

A Receptor-targeted Fluorescent Radiopharmaceutical for Multireporter Sentinel Lymph Node Imaging

Abstract: Purpose:To determine the imaging and receptor-binding properties of a multireporter probe designed for sentinel lymph node (SLN) mapping via nuclear and fluorescence detection. Materials and Methods:The animal experiments were approved by the institutional animal care and use committee. A multireporter probe was synthesized by covalently attaching cyanine 7 (Cy7), a near-infrared cyanine dye, to tilmanocept, a radiopharmaceutical that binds to a receptor specific to recticuloendothelial cells. In vitro binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 31 publications
(32 reference statements)
2
53
1
Order By: Relevance
“…Other hybrid nanoparticles also have the potential to guide SLN biopsy (8). A recent preclinical example of a hybrid SLN tracer can be found in 99m Tc-tilmanocept labeled with the NIR dye Cy7 (9). Alternatively, Cerenkov imaging of positronemitting radionuclides has been proposed as a hybrid imaging technology; Thorek et al demonstrated that LNs could be detected after a subdermal injection of 18 F-FDG in the tail of a mouse (10).…”
Section: (Hybrid) Tracersmentioning
confidence: 99%
“…Other hybrid nanoparticles also have the potential to guide SLN biopsy (8). A recent preclinical example of a hybrid SLN tracer can be found in 99m Tc-tilmanocept labeled with the NIR dye Cy7 (9). Alternatively, Cerenkov imaging of positronemitting radionuclides has been proposed as a hybrid imaging technology; Thorek et al demonstrated that LNs could be detected after a subdermal injection of 18 F-FDG in the tail of a mouse (10).…”
Section: (Hybrid) Tracersmentioning
confidence: 99%
“…The amount of IRDye 800CW within each SLN was calculated based on the amount of 800CW-tilmanocept and the IRDye 800CW density. The percent SLN extraction 23 was calculated as the difference between the SLN and distal lymph node counts divided by the sum of the SLN and distal lymph node counts.…”
Section: Nuclear Counting and Sln Irdye 800cw Calculationmentioning
confidence: 99%
“…After radiolabeling tilmanocept with 68 Ga, a generator-produced positron-emitting radionuclide, canine pelvic SLNs were imaged 1 h after a transrectal injection into the prostate gland. 21 Covalent attachment of Cy7, a cyanine fluorescent dye, to tilmanocept resulted in an NIR fluorescent-tagged tilmanocept, 22,23 which retained the properties exhibited by tilmanocept without the fluorescent tag. Fluorescent-labeled tilmanocept exhibited sub-nanomolar receptor affinity (K D < 1 nM) to a macrophage cell line that expresses the receptor (CD206), as well as in vivo behavior consistent with SLN receptor-mediated accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…If the sentinel lymph node (the first node that drains the tumor) is free of malignant cells, then the remaining lymph nodes should also be free of metastatic disease (59). Conventional sentinel lymph node mapping is performed using 20-to 600-nm radiocolloids (Fig.…”
Section: Nanocolloidalmentioning
confidence: 99%
“…4) (60). A small study using the multireporter probe 99m Tc-labeled Cy7 tilmanocept demonstrated in vitro and in vivo receptor binding properties for successful receptor-targeted sentinel lymph node mapping with nuclear and optical imaging (59). 99m Tc-tilmanocept has a dextran frame linked with multiple diethylenetriaminepentaacetic acid and mannose residues.…”
Section: Nanocolloidalmentioning
confidence: 99%